Studien zur Altägyptischen Kultur, Band 46 - Kahl, Jochem (Studien zur Altägyptischen Kultur, 2017)
Cover -- Inhaltsverzeichnis -- Johannes Auenmüller: Ein Beitrag zur regionalen Prosopografie des Neuen Reiches (II): Das Relief eines Oberrindervorstehers aus Tuna el-Gebel? -- Lucas Baqué-Manzano: Thoth in PT [218] 163d and PT [219] 175a: From the Shadows of Power -- Mahmoud A. Emam / Ehab Abd el-Zaher: Two New Fragments of Ramesses II from the Temple of Behbeit el-Hagar -- Amr Gaber: A Guardian Snake Deity Called Heneb Revealed -- Alina Grams: Der Gefahrenkatalog in den Oracular Amuletic Decrees -- Khaled Hassan: New Literary Compositions of the scribe Amunnakhte son of Ipuy. A study of Hieratic Ostracon in the Egyptian Museum of Cairo -- Jochem Kahl / Ahmed Alansary / Ursula Verhoeven / Tina Beck / Ewa Czyżewska-Zalewska / Eva Gervers / Andrea Kilian: The Asyut Project: Twelfth Season of Fieldwork (2016) -- Antonio J. Morales / Rawda Abd El-Hady / Kelly Accetta / Sergio Alarcón / Teresa Bardají / Flavio Celis / Ernesto Echevarría / Sebastian Falk / Mohamed Hussein / Salima Ikram / Jónatan Ortiz / Mohamed Osman / Ana Sáez / Raúl Sánchez / Dina Serova / Hazem Shared / Kei Yamamoto / Eman H. Zidan: The Middle Kingdom Theban Project: Preliminary report on the University of Alcalá Expedition to Deir el-Bahari, Third Season (2017) -- Martin Odler / Marie Peterková Hlouchová: "May you receive that favourite harpoon of yours..." Old Kingdom spears/harpoons and their contexts of use -- Anastasiia Stupko-Lubczyńska: Reading the Offering Procession in the Chapel of Hatshepsut at Deir el-Bahari -- Toon Sykora: Real or fake? An evaluation of the pre-funerary function of ancient Egyptian chordophones -- Mykola Tarasenko / Mladen Tomorad: The Shabtis from the Museum of Oriental Civilizations in Zolochiv Castle, Ukraine -- Filip Taterka: Were Ancient Egyptian Kings Literate?.